2023
DOI: 10.3389/fnut.2023.1277350
|View full text |Cite
|
Sign up to set email alerts
|

Could vitamin D concentration be a marker of a long hospital stay in older adults patients?

Justyna Nowak,
Marzena Jabczyk,
Paweł Jagielski
et al.

Abstract: Background and aimsVitamin D plays a pleiotropic role in the human body. Some studies have suggested that hypovitaminosis D may serve as a marker of comorbidity severity and length of hospital stay. Hospitalized older adults patients with a higher comorbidity burden tend to have lower vitamin D status, which negatively impacts the length of their hospital stay. Vitamin D deficiency has been identified as a significant risk factor for a prolonged hospital stay. This study aimed to investigate the link between v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous studies showed higher rates of vitamin D deficiency in older patients [ 33 ]. However, not only does the age-dependent reduced synthesis of vitamin D in the skin play a role, but also the increased rate of hospitalizations, immobilization, increased rate of renal insufficiency, and the intake of various medications might affect vitamin D metabolism [ 33 , 34 , 39 , 40 ]. While there have been suggestions that the aging process also might diminish the intestine’s capacity to absorb dietary vitamin D, research has shown that aging does not affect the absorption of both physiological and pharmacological doses of vitamin D [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed higher rates of vitamin D deficiency in older patients [ 33 ]. However, not only does the age-dependent reduced synthesis of vitamin D in the skin play a role, but also the increased rate of hospitalizations, immobilization, increased rate of renal insufficiency, and the intake of various medications might affect vitamin D metabolism [ 33 , 34 , 39 , 40 ]. While there have been suggestions that the aging process also might diminish the intestine’s capacity to absorb dietary vitamin D, research has shown that aging does not affect the absorption of both physiological and pharmacological doses of vitamin D [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%